2020
DOI: 10.1016/j.synbio.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Advances on systems metabolic engineering of Bacillus subtilis as a chassis cell

Abstract: The Gram-positive model bacterium Bacillus subtilis , has been broadly applied in various fields because of its low pathogenicity and strong protein secretion ability, as well as its well-developed fermentation technology. B. subtilis is considered as an attractive host in the field of metabolic engineering, in particular for protein expression and secretion, so it has been well studied and applied in genetic engineering. In this review, we discussed why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…Fajardo-Cavazos and Nicholson reported that freeze-dried B. subtilis spores in capsules can survive up to 3 years, not only in ambient conditions, but also in a round trip voyage to Mars with the presence of Galactic cosmic radiation and solar particle-event radiations [52]. In addition, B. subtilis is easy to modify genetically [78], which makes it easier to design recombinant spores targeting both the original SARS-CoV-2 and mutant viruses (Figure 1). Here, we successfully designed and engineered a type of recombinant B. subtilis, which can express sRBD on the surface of spores by encoding sRBD linked with the CotC gene.…”
Section: Discussionmentioning
confidence: 99%
“…Fajardo-Cavazos and Nicholson reported that freeze-dried B. subtilis spores in capsules can survive up to 3 years, not only in ambient conditions, but also in a round trip voyage to Mars with the presence of Galactic cosmic radiation and solar particle-event radiations [52]. In addition, B. subtilis is easy to modify genetically [78], which makes it easier to design recombinant spores targeting both the original SARS-CoV-2 and mutant viruses (Figure 1). Here, we successfully designed and engineered a type of recombinant B. subtilis, which can express sRBD on the surface of spores by encoding sRBD linked with the CotC gene.…”
Section: Discussionmentioning
confidence: 99%
“…B. subtilis has a short growth cycle, easy fermentation process, high genetic engineering operability, high genetic stability, clear metabolic networks, and no obvious codon preference. Most importantly, it has good protein secretion and expression capacity [42,43]. B. subtilis natto, mainly isolated from the fermented vegetable cheese natto, exhibited a multiple-effect fibrinolytic activity of approximately 40 IU/g (wet weight) [24].…”
Section: Production Strains Of Nkmentioning
confidence: 99%
“… 20 Given the availability of an increasing number of cloning vectors and mutant host lines that are provided by the Bacillus Genetic Stock Center (BGSC), 21 many strains can be transformed using systematic metabolic engineering to obtain mutant strains that meet production requirements. 22 For example, B. subtilis WB600 and B. subtilis WB800 were constructed from B. subtilis 168 by knocking out six and eight protease genes, respectively. 20 , 23 Although some proteases may be of interest to the industry, their activity generally limits the overall efficiency of heterologous protein production.…”
Section: The B Subtilis Expression Platformmentioning
confidence: 99%